Contribución al conocimiento de la brioflora urbana de la ciudad de Badajoz. - Viera Benítez, C.; Ron Álvarez, María Eugenia (Botanica Complutensis, 1986)
Tbe identification of tbe Bryopbyta recorded in tbe town of Badajoz (19821983) has yielded a catalogue of 22 species of mosses and 3 of liverworts. This paper gives information on their occurrence within the town and indicates whicli of them are firstly cited br the province.